DEVELOPMENT OF CANVA DIGITAL BOOKS TO IMPROVE LEARNING OUTCOMES FIFTH GRADE ELEMENTARY SCHOOL STUDENTS - Priska Nurlia Br Simanungkalit; Daulat Saragi; Wildansyah Lubis (Jurnal Cakrawala Pendas, 2025)
The learning outcomes of Civics Education for 5th-grade students at SDN 055981 Beruam are still low due to the lack of variation in learning media used by teachers. This study aims to develop and test the effectiveness of Canva-based digital books in improving student learning outcomes, using the 4D development model with subject matter experts, media, and language experts as validators, as well as teachers as learning practitioners and students. Data were collected through questionnaires to determine validity and practicality, and tests to measure effectiveness. The results showed that the validity of the Canva-based digital book was very feasible with an average of 91.7%, practicality was very high with an average of 90.75% from teachers and students, and effectiveness was in the moderate category with a gain score of 0.56. Thus, the Canva-based digital book developed was declared feasible, practical, and effective, and contributed to the development of learning media in elementary schools.